Armazenamento dos produtos para saúde estéreis no centro de esterilização e unidades assistenciais de hospitais de grande porte de Belo Horizonte - Ivone Coutinho Mussel (2013)
The sterile health product (SHP) when stored in the health care units should be kept in appropriate or similar to the Material and Sterilization Center (MSC) conditions, in order to guarantee both the shelf life and safe of use. Many aspects and challenges in maintaining the sterility for instance, hospital physical characteristics, used packaging type and restricted access may influence the quality of storage of sterile PPS. This study was guided by the following question: What are the conditions for packaging of sterile PPS units in direct assistance and in the MSC? To answer the question, it was proposed as objective: To analyze the conditions of the custody places for sterile products for health care units and large scale hospitals and MSC of Belo Horizonte. This is an exploratory and descriptive study with a quantitative approach. 11 institutions were included. Data were collected by means of an instrument containing aspects related to the physical structure, infrastructure, and organization of the environment as well as storage conditions. Data collection was conducted in the period May to September 2013, data analysis was performed based on the Statistical Package for the Social Sciences, version 19.0 , using descriptive analysis, with the presentation of absolute values and percentages. The characterization of the MSC, based on information obtained from the respondents (100 % nurses) showed the presence of sealed windows (60 %). The minimum required distance was found in the ceiling (100 %) of the institutions, and in (90 %) and distance of the walls (80 %) distance from the ground. As for the packaging of sterile equipment, closed cabinets (60 %) were found, with washable lining (100 %). The control of temperature and relative humidity was referred to as held in all MSC, varying the parameters adopted. The expiration date of the SHP was reported as sterile checked in (100 %) of the MSC. Transport in exclusive cars occurs in 80 % of the institutions. As non-compliance of MSC, it was found that (30 %) did not have sole physical area for materials and sterilized (30 %) they stored sterile SHP along with non-sterile materials. Emergency Care (EC), Surgical Center (SC) and Intensive Care Unit (ICU) to characterize care units of the participating institutions , 33 sectors were visited . Hospitals in the study (54.5 %) of the professionals could not answer any item questionnaire or responded divergently to information provided by nurses form . Were washable (93.9 %) of the units equipment; were in closed cabinets (75.8 %), and the expiration date of sterilization was observed in (97 %) of the units. How nonconformities are cited in the ICU (30 %) in SC (20 %) and EC (30 %) were not unique to the keeping of materials sterilized with no barrier and (3.0%) had no restriction to access. It was concluded that both the MSC as in medical clinics, there was divergence in some conditions of the recommendations of regulatory health agencies for storage of sterile SHP in the institutions surveyed, leading to infer that the current law is not being fully observed.